STANDARDIZATION OF A UNANI PHARMACOPOEIAL TABLET ‘QURS-E-NUQRA’ (AYUSHDHARA, 2017)
There is a global demand for natural plant based products including Unani medicines for various health problems. As such the standardization is burning topic in Unani as well as Ayurvedic drugs manufacturer today. Standardization is an essential measurement for ensuring the quality control. The three steps of standardization during the manufacturing of the drug i.e. raw material, in process and final product standardization. Like any other system of medicine the efficacy of Unani formulations depends on potential and purity of the drugs used. To develop a mechanism for quality assurance of plants products and to ensure the purity of crude drugs and its standardization is essential. Standardization and quality control are the key factors in regulating the therapeutic efficacy because organoleptic parameters are insufficient for quality assessment. The present study deal with compound Unani formulation of ‘Qurs-e-Nuqra’ a tablet formulated on the formullae mentioned in National Formulary of Unani Medicine Part I. For standardization of drugs, investigation of the tablets were made on the basis of the parameters approved by the Unani Pharmacopoea Committe, along with the analysis of pesticidal residue, microbial load, heavy metals and aflotoxin analysis. The Thin layer chromatography (TLC) finger printing was made to check the standard of future batch.